α-Olefin Trimerization for Lubricant Base Oils with Modified Chevron-Phillips Ethylene Trimerization Catalysts - Baek, Jun Won; Ko, Ji Hyeong; Park, Jun Hyeong; Park, Ju Yong; Lee, Hyun Ju; Seo, Yeong Hyun; Lee, Junseong; Lee, Bun Yeoul (Organometallics, 2022)
α-Olefin trimers are used at a bulk scale as top-tier lubricant base oils, with putative future applications as diesel fuels obtainable from renewable ethylene. α-Olefin trimers are conventionally obtained in the cationic oligomerization process, during which a range of n-mers are simultaneously generated alongside severe skeleton rearrangement. In this context, catalysts that can selectively convert α-olefin to its trimers are valuable. However, few examples have been reported. Herein, we report selective α-olefin trimerization catalysts constructed via the modification of the Chevron-Phillips ethylene trimerization catalytic system and avoiding the use of expensive activators, such as methylaluminoxane (MAO), B(C6F5)3, and [B(C6F5)4]-salt, despite the typical Chevron-Phillips system being inactive for α-olefin. A catalytic system Cr(acac)3/[2,5-Me2C4H2N-Al(iBu)3]-Na+/(iBu)3Al demonstrating high turnover numbers exceeding 10,000 (31 kg/g-Cr for 1-decene), generating trimers selectively without other higher or lower fractions, was developed, confirmed by simulated distillation gas chromatography analysis. The hypothesized η5-pyrrolide chromium active species was partially confirmed by the structure elucidation of [η5-Me2C4H2N-AlMe3]Cr(Me)[CH2C6H4(ortho-NMe2)-κ2C,N]. The prepared 1-decene trimers (after hydrogenation) exhibited an advantageously higher viscosity index than the commercial product PAO-4.0 (128 vs 123). Fluids demonstrating similar lubricant characteristics to either the 1-decene trimers or PAO-4.0 were obtained by using a 1-octene/1-dodecene blend.
Keywords: 1-decene; Catalytic system; Cationics; Chevron Phillips; Ethylene trimerization; Future applications; Lubricant base oil; Oligomerizations; Trimerization; Trimerization catalysts